Urban sound classification using convolutional Neural Network and long short term memory based on multiple features - Das, Joy Krishan; Ghosh, Arka; Pal, Abhijit Kumar; Dutta, Sumit (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.